Analisis Intellectual Quotient (IQ), Emotional Quotient (EQ), dan Spiritual Quotient (SQ) Terhadap Kinerja Karyawan Rumah Sakit Baptis Kediri - Nanda Jwinita Widi Karana; Eka Askafi; Mohammad Naim Musafik (Otonomi, 2022)
This study aims to analyze whether: (1) there is an influence of Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ)on the performance of Baptis Hospital employees of Kediri district. The study used is a quantitative approach by using survey method. The data analysis used by using applied SPSS Program 23 Version assistance. The respondents as samples are 67 employee. The results revealed that: (1) simultaneously Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ) influence on the performance of Baptis Hospital employees of Kediri district. (2) Partially, Intellectual Quotient (IQ) influence on the performance of Baptis Hospital employees of Kediri district, and (3) Emotional Quotient (EQ) influence on the performance of Baptis Hospital employees of Kediri district, and (4) Spiritual Quotient (SQ) influence on the performance of Baptis Hospital employees of Kediri district. It is recommended that the head of Baptis Hospital should increase employee’s IQ, EQ and SQ.